Progress and inequities in maternal mortality in Afghanistan (RAMOS-II): a retrospective observational study. Issue 5 (May 2017) - Bartlett, Linda; LeFevre, Amnesty; Zimmerman, Linnea; Saeedzai, Sayed Ataullah; Torkamani, Sabera; Zabih, Weeda; Tappis, Hannah; Becker, Stan; Winch, Peter; Koblinsky, Marge; Rahmanzai, Ahmed Javed
Summary: Background: The risk of maternal death in Afghanistan is among the highest in the world; however, the risks within the country are poorly understood. Subnational maternal mortality estimates are needed along with a broader understanding of determinants to guide future maternal health programmes. Here we aimed to study maternal mortality risk and causes, care-seeking patterns, and costs within the country. Methods: We did a household survey (RAMOS-II) in the urban area of Kabul city and the rural area of Ragh, Badakshan. Questionnaires were administered to senior female household members and data were collected by a team of female interviewers with secondary school education. Information was collected about all deaths, livebirths, stillbirths, health-care access and costs, household income, and assets. Births were documented using a pregnancy history. We investigated all deaths in women of reproductive age (12–49 years) since January, 2008, using verbal autopsy. Community members; service providers; and district, provincial, and national officials in each district were interviewed to elicit perceptions of changes in maternal mortality risk and health service provision, along with programme and policy documentation of maternal care coverage. Findings: Data were collected between March 2, 2011, and Oct 16, 2011, from 130 688 participants: 63 329 in Kabul and 67 359 in Ragh. The maternal mortality ratio in Ragh was quadruple that in Kabul (713 per 100 000 livebirths, 95% CI 553–873 in Ragh vs 166, 63–270 in Kabul). We recorded similar patterns for all other maternal death indicators, including the maternal mortality rate (1·7 per 1000 women of reproductive age, 95% CI 1·3–2·1 in Ragh vs 0·2, 0·1–0·3 in Kabul). Infant mortality also differed significantly between the two areas (115·5 per 1000 livebirths, 95% CI 108·6–122·3 in Ragh vs 24·8, 20·5–29·0 in Kabul). In Kabul, 5594 (82%) of 6789 women reported a skilled attendant during recent deliveries compared with 381 (3%) of 11 366 women in Ragh. An estimated 85% of women in Kabul and 47% in Ragh incurred delivery costs (mean US66·20, IQR 61·30 in Kabul and 9·89, 11·87 in Ragh). Maternal complications were the third leading cause of death in women of reproductive age in Kabul, and the leading cause in Ragh, and were mainly due to hypertensive diseases of pregnancy. The maternal mortality rate decreased significantly between 2002 and 2011 in both Kabul (by 71%) and Ragh (by 84%), plus all other maternal mortality indicators in Ragh. Interpretation: Remarkable maternal and other mortality reductions have occurred in Afghanistan, but the disparity between urban and rural sites is alarming, with all maternal mortality indicators significantly higher in Ragh than in Kabul. Customised service delivery is needed to ensure parity for different geographic and security settings. Funding: United States Agency for International Development (USAID).